Islet damage during isolation as assessed by miRNAs and the correlation of miRNA levels with posttransplantation outcome in islet autotransplantation. Issue 4 (8th January 2018) - Saravanan, Prathab Balaji; Kanak, Mazhar A.; Chang, Charles A.; Darden, Carly; Yoshimatsu, Gumpei; Lawrence, Michael C.; Naziruddin, Bashoo
Abstract : High‐quality pancreatic islets are essential for better posttransplantation endocrine function in total pancreatectomy with islet autotransplantation (TPIAT), yet stress during the isolation process affects quality and yield. We analyzed islet‐enriched microRNAs (miRNAs) ‐375 and ‐200c released during isolation to assess damage and correlated the data with posttransplantation endocrine function. The absolute concentration of miR‐375, miR‐200c, and C‐peptide was measured in various islet isolation steps, including digestion, dilution, recombination, purification, and bagging, in 12 cases of TPIAT. Posttransplantation glycemic control was monitored through C‐peptide, hemoglobin A1c, insulin requirement, and SUITO index. The amount of miR‐375 released was significantly higher during enzymatic digestion followed by the islet bagging ( P  <   .001). Mir‐200c mirrored these changes, albeit at lower concentrations. In contrast, the C‐peptide amount was significantly higher in the purification and bagging steps ( P  <   .001). Lower amounts of miR‐375 were associated with a lower 6‐month insulin requirement ( P  =   .01) and lower hemoglobin A1c ( P  =   .04). Measurement of the absolute quantity of miRNA‐375 and ‐200c released during islet isolation is a useful tool to assess islet damage. The quantity of released miRNA is indicative of posttransplantation endocrine function in TPIAT patients. Abstract : Quantification of microRNA‐375 released during islet isolation procedures demonstrates islet damage and indicates posttransplant endocrine function in patients undergoing total pancreatectomy with islet autotransplantation.